TINJAUAN YURIDIS EKSISTENSI KOMISI PENGAWAS PERSAINGAN USAHA (KPPU) - Endang Retnowati (Perspektif, 2004)
In terms of enforcement of Act No. 5 year l999 on prohibition on practices of unhealthy enterprise and monopoly, thus a special institution has been established to oversee behaviours of enterprise agents namely Supervising Committee by Unhealthy Competition (KPPU). Yet existence of KPPU as arranged in Act No. 5 year 1999 do not specifically account for their authority so that in eject they considerably encounter remarkably crucial obstacles. Existence of KPPU is really required yet it must be based on proper legal regulations as foundation of KPPU existence per se.